On the spectrum of the negative Laplacian for general doubly-connected bounded domains - E. M. E. Zayed; A. I. Younis (International Journal of Mathematics and Mathematical Sciences)
This paper is devoted to asymptotic formulas for functions related with the spectrum of the standard Laplace operator in two and three dimensional bounded doubly connected domains with impedance boundary conditions, where the impedances are assumed to be positive functions. Moreover, asymptotic expressions for the difference of eigenvalues related to impedance boundary value problems with different impedances are derived. Further results may be obtained.